Attitudes of cancer patients and their families toward disclosure of cancer diagnosis in Saudi Arabia: a Middle Eastern population example - Alzahrani, Ahmad S (Patient Prefer Adherence, 2018)
OBJECTIVES: Particularly in the Middle East, few studies have explored the attitude of cancer patients and their families toward cancer diagnosis disclosure (CDD). This study was conducted to investigate the preference and attitude of a sample of cancer patients and their families in Saudi Arabia toward CDD. METHODS: We constructed a questionnaire based on previous studies. The questionnaire assessed preference and attitude toward CDD. Participants were recruited from the King Abdullah Medical City, which has one of the largest cancer centers in Saudi Arabia. RESULTS: Three hundred and four cancer patients and 277 of their family members participated in the study. The patient group preferred CDD more than the family group (82.6% vs 75.3%, P<0.05). This preference is especially more evident toward disclosure of detailed cancer information (status, prognosis, and treatment) (83.6% vs 59.9%, P<0.001). In a binary logistic regression, factors associated with preference toward CDD included having information about cancer (odds ratio [OR] 1.8; 95% confidence interval [CI], 1.15–2.84) and being employed (OR, 1.77; 95% CI, 1–2.82) while being from the patient group was the only factor associated with preference toward detailed cancer information (OR, 3.25; 95% CI, 2.11–5.05). In terms of patient reaction after CDD, “fear” was the attitude expected by the family group more than the patient group (56.3% vs 70.4%, P<0.001) while “acceptance” was the attitude anticipated by the patient group more than the family group (38% vs 15.2%, P<0.001). CONCLUSION: Patients preferred CDD and disclosure of related information, while their families were more inclined toward scarce disclosure. Family members seem to experience negative attitudes more than the patients themselves.